Environmental policies & media reporting in Malaysia / Mohd Hamdan Adnan - Adnan, Mohd Hamdan (Faculty of Communication and Media Studies (FCMS), 1993)
Everytime the Malaysian environment is being discussed internationally, the picture that is usually painted is of wanton felling of tress with scant respect for the ecology and the environment as well as her own indigenous people. The mass media of developed nations have aggravated this picture of Malaysia.